2009
DOI: 10.1053/j.gastro.2009.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Extracellular pH Sensitizes the Acinar Cell to Secretagogue-Induced Pancreatitis Responses in Rats

Abstract: Background and Aims-Protease activation within the pancreatic acinar cell is a key early event in acute pancreatitis and may require low pH intracellular compartments. Clinical studies suggest that acidosis may affect the risk for developing pancreatitis. We hypothesized that exposure to an acid load might sensitize the acinar cell to secretagogue-induced pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 33 publications
2
60
0
1
Order By: Relevance
“…2 Inhibition of vATPase with the classic vATPase inhibitors bafilomycin-A1 and concanamycin-A not only inhibits CER-stimulated zymogen activation, 2 but also blocks the enhancing effect of an extracellular acid load in vitro. 23 Because the classic vATPase inhibitors bafilomycin and concanamycin have been shown to have nonspecific effects, [6][7][8][9] the current study was undertaken to confirm our previous results utilizing the novel class of vATPase inhibitors, the benzolactone enamides, which have a different mode of inhibition, as well as genetic manipulation using siRNA.…”
Section: Open Access Animal Physiology Downloaded From Https://wwwdosupporting
confidence: 59%
See 1 more Smart Citation
“…2 Inhibition of vATPase with the classic vATPase inhibitors bafilomycin-A1 and concanamycin-A not only inhibits CER-stimulated zymogen activation, 2 but also blocks the enhancing effect of an extracellular acid load in vitro. 23 Because the classic vATPase inhibitors bafilomycin and concanamycin have been shown to have nonspecific effects, [6][7][8][9] the current study was undertaken to confirm our previous results utilizing the novel class of vATPase inhibitors, the benzolactone enamides, which have a different mode of inhibition, as well as genetic manipulation using siRNA.…”
Section: Open Access Animal Physiology Downloaded From Https://wwwdosupporting
confidence: 59%
“…Our laboratory has shown that reducing extracellular or intracellular pH enhances secretagogue stimulated zymogen activation both in vitro and in vivo. 23 In addition, the lysosomal hydrolase cathepsin-B has been shown to activate trypsinogen 24,25 and this activation requires a low pH environment. 26 Furthermore, cathepsins have been shown to colocalize with digestive zymogens 27,28 and the zymogen activation compartment may be lysosomally derived and/or associated with the secretory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This results in edema, vascular damage, hemorrhage and cell death (18,19). In addition to oxidative stress (20) and calcium overload (21), hypotension (22) and low acinar pH (23) contribute to these initiation processes. After initial production of active pancreatic enzymes, local cell death and systemic inflammation ensue.…”
Section: Introductionmentioning
confidence: 99%
“…Intraluminal pH is also play a central role in normal pancreatic functions, since luminal acidosis may elevate the risk of AP [55,56]. Different etiological factors also can contribute to the development of AP such as excessive ethanol consumption, smoking, viral infections and also gallstones [57][58][59][60][61].…”
Section: Pancreasmentioning
confidence: 99%